Impact on health‐related quality of life and symptoms of anxiety and depression after 32 weeks of Dupilumab treatment for moderate‐to‐severe atopic dermatitis. Issue 5 (3rd March 2022) - Miniotti, Marco; Lazzarin, Giulia; Ortoncelli, Michela; Mastorino, Luca; Ribero, Simone; Leombruni, Paolo
Abstract: Dupilumab is the first biological agent approved for treatment of moderate‐to‐severe atopic dermatitis (AD). Evidence of Dupilumab effectiveness on psychological outcomes beyond 16 weeks of treatment from real‐life settings is lacking. To evaluate the effectiveness of Dupilumab treatment up to 32 weeks, focusing health‐related quality of life and psychological outcome of patients with moderate‐to‐severe AD. An observational prospective cohort study was conducted in a real‐life setting at an Italian tertiary centre. Assessment of outcome measures was carried out at baseline, after 16 and 32 weeks of treatment. A total of 171 patients were included. EASI‐75 and EASI‐90 were achieved in 85% and 60% of the participants, respectively, after 16 weeks, and in 89.6% and 69.8% after 32 weeks of treatment. Significant improvements ( p  < 0.001; r  = 0.57–0.95) were found after 16 weeks for each outcome considered, including clinician and patient‐reported measures of AD severity and scales of health‐related quality of life and psychological morbidity, and maintained up to 32 weeks. Further analysis revealed that patients' quality of life was more associated with the subjective perception of disease severity rather than objective measures and suggested a possible different response to treatment based on the age of AD onset. Dupilumab was confirmed to be rapid, effective and safe in patients with moderate‐to‐severe AD. Its positive impact on psychological outcomes up to 32 weeks was ascertained here, adding new evidence on the need to consider subjective factors affecting patients' perception of disease severity in evaluating the response to treatment.